General characteristics and structure of environmental risks in the subsoil use sphere (Journal of actual problems of jurisprudence, 2019)
This article examines the nature, types and structure of environmental risks in the mineral resources. It was determinedthat the variety of risks associated with the environment described in a single term - environmental risks. Under theenvironmental risk is commonly understood in advance of the estimated probability of occurrence and severity in agiven anthropogenic interference with the natural environment of such violations, which may be unfavorable to thecontinued functioning of ecological systems and the existence of a direct field of human impact, and beyond. It is shownthat the work carried out in the mineral resources have a significant impact on the environment. Based on the researchthe author gives a complete definition of environmental risk, formulated its basic characteristics and structural elementsKey words: environmental risks, market economics, geology, subsoil insurance.